If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18 + -6x = 9x Solving 18 + -6x = 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. 18 + -6x + -9x = 9x + -9x Combine like terms: -6x + -9x = -15x 18 + -15x = 9x + -9x Combine like terms: 9x + -9x = 0 18 + -15x = 0 Add '-18' to each side of the equation. 18 + -18 + -15x = 0 + -18 Combine like terms: 18 + -18 = 0 0 + -15x = 0 + -18 -15x = 0 + -18 Combine like terms: 0 + -18 = -18 -15x = -18 Divide each side by '-15'. x = 1.2 Simplifying x = 1.2
| 40=t+70t | | x^2+3y^2-7=0 | | Q=2p-2 | | -119-4x=31+x | | x-26=-17 | | 125m-75+43200=46125-175 | | 5x-3+13=40 | | 5(x-6)+7x=7x-10 | | 4x(2)=121 | | x^2+y^2+8x-8y-13=0 | | 8d+103=210 | | (g+4)-3g=1+1 | | 12x+10-1=45 | | -23-x=-8 | | 6(x-3)=35 | | 45+n=10n | | 5p^2=-7+10p | | 4x+9x-19=95-6x | | x^2-4x=-45 | | 3(a-4)=2(q+5) | | -22=-11z | | x-5-3r=17 | | -10x-5x=-7 | | x+9=5(x-2) | | -0.96j=-0.73 | | y^7+2y^3-10y^2=0 | | m^2-6m-26=0 | | 120=2nxm*p | | 8p^2*4p= | | 8-7x-4=-18+4x-11 | | 9-5(u-2)=3(2u-1) | | 8c+8=244 |